Análise e desenvolvimento de um sistema de transferência de energia sem fio aplicado na recarga de veículos elétricos - Viera, Leonardo Antonio Brum (2022)
Technologies related to the electrification of means of transport have been gaining ground in recent years. This development is motivated by environmental and economic factors. Among the technologies explored, the main ones are the charging system for electric vehicles and the energy storage system. The most used charging system is the conductive system, however, it presents problems related to the user’s practicality and health. In this way, wireless battery charger solutions arise. In view of this, the present work presents the study, analysis, design and implementation of a converter for wireless battery chargers. The work begins with the review and analysis of wireless energy transmission technologies, as well as the study of the architecture of a charger and the converters used in the process. A design methodology is presented which uses an optimized algorithm for dimensioning the basic components of the system, aiming at the operation with maximum performance. A 3.6 kW wireless power converter topology is then proposed, which was designed and built in practice. Through experimental tests, a maximum efficiency of 89.4 % was obtained for transmission at a distance of 16 cm.